Production, Purification and Characterization of a novel L-asparaginase from Acinetobacter baumannii with anticancerous activity (International Journal of Current Engineering and Technology, 2014)
L-asparaginase is an enzyme that catalyzes the conversion of L-asparagine to L-aspartate and ammonia. The important application of the L-asparaginase enzyme in using it as chemotherapeutic for its anticarcinogenic potential .In the present study a novel strain, AcinetobacterbaumanniiR7 was explored for the production of extra- cellular L-asparaginase .This enzyme was purified by single chromatography step to homogenicity with a recovery yield of 77% and 92.9 fold of purification by using isopropanol (1:2) and CM-Sephadex C-50 chromatography. The enzyme appeared as a single protein band on SDS-PAGE gel with a molecular mass corresponding to 160 kDa. The Purified enzyme does not possess any glutaminase activity. The Kmwas calculated as 22 mg/ml and Vmaxas 625 U/mg of protein using L-asparagine as substrate. L-asparaginase purified from AcinetobacterbaumanniiR7 at a concentration of 0.2 mg/ml showed better toxicity on OAW-42 cell line (59 and 51 % survival) for 24 and 48 h, respectively, in comparison with controls, and this result led to increase the benefit by using the enzyme for the treatment of human ovarian cancer.
Keywords: L-asparaginase, AcinetobacterbaumanniiR7, anticancerous activity